2015
DOI: 10.1080/13691058.2015.1116125
|View full text |Cite
|
Sign up to set email alerts
|

Family and cultural influences on cervical cancer screening among immigrant Latinas in Miami-Dade County, USA

Abstract: Cervical cancer disproportionately affects minorities, immigrants and low-income women in the USA, with disparities greatest among Latino immigrants. We examined barriers and facilitators to cervical cancer screening practices among a group of immigrant Latino women in Florida, USA. Between January and May 2013, six focus group discussions, involving 35 participants, were conducted among Hispanic women in Miami to explore their knowledge, beliefs about cervical cancer and facilitators and barriers to cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Therefore, it is urgent to solve the problem of low screening rates. Previous studies have found that internal cognitive behavior factors, external social influencing factors, cervical cancer knowledge, and some demographic variables are the important influencing factors related to the behavior intentions for cervical cancer screening [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. This information may provide direction and methods for interventions to investigate how these factors influence the behavior intentions related to cervical cancer screening among Chinese women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is urgent to solve the problem of low screening rates. Previous studies have found that internal cognitive behavior factors, external social influencing factors, cervical cancer knowledge, and some demographic variables are the important influencing factors related to the behavior intentions for cervical cancer screening [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. This information may provide direction and methods for interventions to investigate how these factors influence the behavior intentions related to cervical cancer screening among Chinese women.…”
Section: Introductionmentioning
confidence: 99%
“…Kristiansen et al (2012) and Ogunwal et al (2016) revealed that support from surrounding populations, male partners, and family members increased women’s participation in cervical cancer screening [13,14]. Madhivanan et al (2016) demonstrated that family factors and education affected the use of cervical cancer screening services for Latin Miami immigrants [15]. The support of female family members was an important factor in promoting screening.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to recent research as authors report that the family is both a barrier and a facilitator. Family can have a positive impact on cervical cancer screening, as well as be a barrier when the “family first” way of life takes priority over self-care (Madhivanan, Valderrama, Krupp, & Ibanez, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Families can contribute to the prevention of cervical cancer by providing support and motivation (Fallahi, Shahrbabaki, Hashemian, & Kahanali, 2016). Family support, especially from female relatives, provides encouragement and motivation for individuals to perform a pap smear test (Madhivanan, Valderrama, Krupp, & Ibanez, 2015). Prevention efforts that are sufficient in the region are supported by the regions' existing additional service for cervical cancer prevention conducted by health workers.…”
Section: Discussionmentioning
confidence: 99%